The "malaise" that has no name: women researchers in COVID19 times - Gómez-Suárez, Águeda; Vázquez-Silva, Iria (Acciones e Investigaciones Sociales, 2021)
In the current pandemic context, a very worrying scenario of inequality between women and men emerges as a result of the inequalities that have worsened during this global pandemic.  This article examines how the COVID-19 pandemic has impacted the existing gender gap in science and the consequences this has had on the health and quality of life of women academics. Through the analysis of several studies carried out in our country and the international scientific literature, it is concluded that confinement has accelerated inequality between male and female academics, mainly as a result of the "care gap" and the sexist division of labour that still survives in academia, leading to deterioration and deterioration of the working conditions of female researchers: more exhaustion, less sleep, more fatigue, more hours of academic teleworking, reproductive and care work and less time available for themselves, and consequently, less scientific production compared to their male colleagues, with the future consequences in the wage gap that this will mean.
Keywords: Gender gap; COVID19-19; Care; Science; Sexism; Women's health.